2009
DOI: 10.1128/aem.01707-08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Approach to Determining the Contribution of Viable-but-Nonculturable Subpopulations to Malolactic Fermentation Processes

Abstract: Different sizes of viable-but-nonculturable cell subpopulations of a lactic acid bacterium strain were induced by adding increasing amounts of SO 2 . The experimental data obtained here were fitted to a segregated kinetic model developed previously. This procedure allowed us to determine in quantitative terms the contribution of this physiological state to malolactic fermentation.The persistence of stressed, damaged, or viable-but-nonculturable (VBNC) cells during microbial fermentation underlines the requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Multiparameter FC analysis represents an important tool in winemaking because it allows monitoring industrial fermentation in real time. According to our knowledge, it has been already used to monitor alcoholic fermentation by Saccharomyces cerevisiae in winemaking (Farthing et al 2007), ethanol stresses in Oenococcus oeni (da Silveira et al 2002) and MLF in cider carried out by Lactobacillus hilgardii (Quir os et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Multiparameter FC analysis represents an important tool in winemaking because it allows monitoring industrial fermentation in real time. According to our knowledge, it has been already used to monitor alcoholic fermentation by Saccharomyces cerevisiae in winemaking (Farthing et al 2007), ethanol stresses in Oenococcus oeni (da Silveira et al 2002) and MLF in cider carried out by Lactobacillus hilgardii (Quir os et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…), the efficiency of different preservation and production processes and products shelf-life [4]. These cells could take an active part in bioprocesses progress and contribute actively to fermentations [8,21,29]. It has been reported that VBNC cells conducting malolactic fermentation showed a state of reduced metabolic activity and that the specific malate uptake rate of the VBNC subpopulation was approximately 50% of that found for the viable population [29].…”
Section: Interest Of the Methodsmentioning
confidence: 98%
“…These cells could take an active part in bioprocesses progress and contribute actively to fermentations [8,21,29]. It has been reported that VBNC cells conducting malolactic fermentation showed a state of reduced metabolic activity and that the specific malate uptake rate of the VBNC subpopulation was approximately 50% of that found for the viable population [29]. VBNC cells may also show undesirable activity or alter endproduct quality [30,31].…”
Section: Interest Of the Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…These kinetic models describe the temporal evolution of the concentration of microorganisms in a system, as a function of relevant intrinsic or extrinsic variables based on different stages of viability (Herrero et al, 2006;Marks, 2008;Quiros et al, 2007;Quiros et al, 2009). …”
Section: Introductionmentioning
confidence: 99%